Design of Functional Powdered Beverages Containing Co-Microcapsules of Sacha Inchi P. huayllabambana Oil and Antioxidant Extracts of Camu Camu and Mango Skins - Nancy Chasquibol; Rafael Alarcón; Billy Francisco Gonzales; Axel Sotelo; Lourdes Landoni; Gabriela Gallardo; Belén García; M. Carmen Pérez-Camino (MDPI AG, 2022)
Sacha inchi Plukenetia huayllabambana oil (SIPHO) was co-microencapsulated, by spray drying using gum arabic as a coating material, with antioxidant extracts of camu camu (Myrciaria dubia (HBK) McVaugh) (CCSE) and mango (Mangifera indica) (MSE) skins obtained by ultrasound-microwave-assisted extraction (UMAE). The physicochemical characteristics of the microcapsules, such as, particle size, morphology, and moisture, as well as the encapsulation efficiency, the fatty acid composition, and oxidative stability, were determined in order to select the best formulation for the design of functional powdered beverages. The formulation with the highest amounts of ω3 acids and polyphenols was used to prepare a functional powdered beverage that contained ω3 (52.74%), antioxidant activity (324.80 mg AAE/100 g powder), and acceptable sensory attributes.